2020
DOI: 10.1177/0300060520926006
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokine expression, platelet-to-lymphocyte ratio and TGF-β1/Smad signaling activity in diabetic patients complicated with pulmonary infection

Abstract: Objective To investigate adipocytokine expression levels, platelet-to-lymphocyte ratio (PLR) and transforming growth factor (TGF)-β1/Smad signaling activity in diabetic patients with pulmonary infection. Methods Eighty-two type 2 diabetic patients with pulmonary infection were included in the observation group and 75 patients with simple type 2 diabetes were recruited into the control group. The fasting blood glucose (FBG), glycated hemoglobin (HbA1c), and PLR in the two groups were compared. Complement-C1q/tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…CTRP9 improved cell viability and attenuated oxidative stress and apoptosis by activating AMPK/nuclear factor, erythroid 2 like 2 pathway in high glucose induced ARPE-19 cells (Cheng et al, 2020), suggesting CTRP9 may be a promising functional target for the treatment and prevention of DR. Otherwise, serum CTRP9 levels decreased significantly in T2DM patients with pulmonary infection (Zha et al, 2020). Serum levels of CTRP9 during the first trimester of pregnancy were significantly decreased in patients with gestational diabetes mellitus compared with those in healthy individuals and were negatively correlated with the BMI or oral glucose tolerance test (Na and Ji, 2020), which was corresponded to the research performed by Xia et al (2020).…”
Section: Diabetesmentioning
confidence: 57%
“…CTRP9 improved cell viability and attenuated oxidative stress and apoptosis by activating AMPK/nuclear factor, erythroid 2 like 2 pathway in high glucose induced ARPE-19 cells (Cheng et al, 2020), suggesting CTRP9 may be a promising functional target for the treatment and prevention of DR. Otherwise, serum CTRP9 levels decreased significantly in T2DM patients with pulmonary infection (Zha et al, 2020). Serum levels of CTRP9 during the first trimester of pregnancy were significantly decreased in patients with gestational diabetes mellitus compared with those in healthy individuals and were negatively correlated with the BMI or oral glucose tolerance test (Na and Ji, 2020), which was corresponded to the research performed by Xia et al (2020).…”
Section: Diabetesmentioning
confidence: 57%
“…Besides, the results of a clinical study demonstrated that serum levels of CTRP9 were significantly diminished in diabetic patients with pulmonary infection 82 and the first trimester of pregnancy among women with gestational diabetes 83,84 85 .…”
Section: The Prognostic Potential Of Ctrp9 Regarding Metabolic Disord...mentioning
confidence: 98%
“…Besides, the results of a clinical study demonstrated that serum levels of CTRP9 were significantly diminished in diabetic patients with pulmonary infection 82 and the first trimester of pregnancy among women with gestational diabetes. 83 , 84 Notably, CTRP9 exerted a protective role against diabetic nephropathy, as well as kidney fibrosis in vivo by inhibiting glomerular and tubular glycogen accumulation, apoptosis, and hyperglycaemia‐mediated oxidative stress.…”
Section: The Prognostic Potential Of Ctrp9 Regarding Metabolic Disord...mentioning
confidence: 98%
See 1 more Smart Citation